Tribological properties of chemically modified diamond like carbon films in hydrogen plasma. (January 2015) - Polaki, S.R.; Kumar, N.; Gopala Krishna, Nanda; Ravindran, T.R.; Kamruddin, M.; Dash, S.; Tyagi, A.K.
Abstract: Diamond like carbon (DLC) films were deposited on silicon substrates by plasma enhanced chemical vapor deposition (PECVD) technique and chemically modified by H2 plasma treatment. The Raman spectra and XPS analysis, revealed a decrease in sp 2 C=C/sp 3 C–C ratio with increase in H2 plasma exposure duration up to 30 min. This is due to the etching of sp 2 C=C sites by hydrogen ions/radicals during plasma treatment. However, this ratio increased fairly for longer H2 plasma exposure time. This might be due to the stabilization of sp 2 C=C bonding by passivation of film surface by hydrogenation. Friction coefficient of these films is found to decrease with an increase in sp 2 C=C fraction. Highlights: I (D)/ I (G) ratio in the DLC film is modified by hydrogen plasma treatment. Hydrogen plasma treated DLC film shows hydrophilic nature due to increase in chemical reactivity. Ultra low friction coefficient is observed in DLC film due to high fraction of sp 2 C=C bonding.